2021
DOI: 10.3390/ijms22189899
|View full text |Cite
|
Sign up to set email alerts
|

Wood Formation under Severe Drought Invokes Adjustment of the Hormonal and Transcriptional Landscape in Poplar

Abstract: Drought is a severe environmental stress that exerts negative effects on plant growth. In trees, drought leads to reduced secondary growth and altered wood anatomy. The mechanisms underlying wood stress adaptation are not well understood. Here, we investigated the physiological, anatomical, hormonal, and transcriptional responses of poplar to strong drought. Drought-stressed xylem was characterized by higher vessel frequencies, smaller vessel lumina, and thicker secondary fiber cell walls. These changes were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 132 publications
0
16
0
Order By: Relevance
“…Further, the more pronounced degree of differences in the chemical composition of bark than wood suggests that the bark is more sensitive to the environment than the wood. More specifically, changes in the contents of the cellulose, lignin and substances soluble in EtOH of bark of trees growing under three environmental stresses revealed that trees adopt certain physiological mechanisms to cope with the abiotic stresses [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the more pronounced degree of differences in the chemical composition of bark than wood suggests that the bark is more sensitive to the environment than the wood. More specifically, changes in the contents of the cellulose, lignin and substances soluble in EtOH of bark of trees growing under three environmental stresses revealed that trees adopt certain physiological mechanisms to cope with the abiotic stresses [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xylem sap of high ammonium-fed poplars contained the highest PIP and NHP levels, whereas NHP was not significantly affected by low and medium nitrate supply, and was not detected under high nitrate supply (Figure 3d,e). ABA, which is important to coordinate the plant's stature and acclimation to drought (Fujita et al, 2005;Yu et al, 2019;Yu et al, 2021), was unaffected by differences in N supply in poplar xylem sap (Figure 3f). S3.…”
Section: Ammonium-and Nitrate-feeding Impact Phytohormones In the Xyl...mentioning
confidence: 99%
“…1a). The diameter and shape of the SCWs are thought to influence hydraulic conductance, and the xylem shape correlates with drought resistance in many different species (Arend & Fromm, 2007; Awad et al ., 2010; Tang et al ., 2018; Yu et al ., 2021). Recently, we and others showed that xylem formation is plastic and responds to water availability.…”
Section: Introductionmentioning
confidence: 99%